Proses Pelaksanaan Penyelesaian Perselisihan Di Lembaga Peradilan Adat Aceh Tingkat Gampong (Desa) - Amdani, Yusi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Customary and Adat law is one of the “directional tool” in determining attitudes and behavior within the limits that have been justified by customary law. The aim in this paper is to examine the legal basic, the principles and objectives Indigenous justice, structure and scope of responsibilities of Indigenous leaders, and enforcement of Indigenous justice. The methode used in this paper are normative and empirical legal research. Legal dispute settlement arrangements in the Aceh Indigenous Judiciary 4th sila Pancasila and this has been recognized by the National Law of Indonesia. Customary justice aims to create balance and peace in society, protecting the rights of victims of crime and people can live in harmony back disputing. The device consists of a village justice element of village government, scholars, intellectuals and other traditional leaders. The implementation of the decision by Keuchik done in a ceremony set at a time mutually agreed.